ICTP, Trieste University, italian and croatian medical physics: A training opportunity for young physicists from developing countries. (September 2016) - Padovani, R.; Longo, R.; Bertocchi, L.; Milotti, E.; Rigon, L.; Denaro, M. De; Brambilla, M.; Capra, E.; Cavedon, C.; Francescon, P.; Hrsak, H.; Foti, C.; et al.
Abstract : Introduction: The Abdus Salam International Centre for Theoretical Physics (ICTP) and the Trieste University have initiated in 2014 a Master of Advanced Studies in Medical Physics a two-years training programme in Medical Physics. The programme is designated to provide young promising graduates in physics, mainly from developing countries, with a post-graduated theoretical and clinical training suitable to be recognised as Clinical Medical Physicist in their countries. Presently, the 3 cycles of the programme has seen 49 participants from 33 Countries: Africa (19), Asia (11), Central and South America (14), and Europe (5), selected from more than 400 applicants per year. Scholarships are awarded to candidates from developing countries with support of the IAEA, TWAS, KFAS, IOMP, EFOMP and ICTP. Material and methods: The programme is developed following the recommendations of IOMP and IAEA for education and clinical training. In the first year 332 lectures and 228 h of exercises are devoted to all main fields of medical physics. The second year is spent in one of the 12 medical physics department of the hospitals' network for the clinical training in: radiation oncology or diagnostic and nuclear medicine, on a programme developed adapting the IAEA (TCS37, TCS47 and TCS50) and AFRA guidelines. Conclusions: IOMP, EFOMP and IAEA are seeing this initiative as an answer to the growing demand of Medical Physicists in developing Countries, representing an important European contribution to the development of medical physics in the developing world.